2020
DOI: 10.3390/nano10061207
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Antibacterial Activity of Silver Nanoparticle-Loaded Graphene Oxide Nanosheets

Abstract: A series of graphene oxide (GO) suspensions with different particle sizes (<100 nm, ~100 nm, ~1 µm and >1 µm) were successfully fabricated after 0, 30, 60 and 120 min of sonication, respectively. The antibacterial properties of GO suspensions showed that >1 µm GO size resulted in a loss of nearly 50% of bacterial viability, which was higher than treatment by ~100 nm GO size (25%) towards Escherichia coli (E. coli). Complete entrapment of bacteria by the larger GO was observed in transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…The detailed procedure for GO synthesis was provided in the Supplementary Information (Section S1) . The nanometric GO was prepared by the probe sonication method [ 30 ]. The prepared GO was then dispersed in DI water to obtain a GO colloidal solution and probe-sonicated for 120 min via ultra-probe sonicator (Qsonica, Sunway Scientific Corporation, Hsinchu, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed procedure for GO synthesis was provided in the Supplementary Information (Section S1) . The nanometric GO was prepared by the probe sonication method [ 30 ]. The prepared GO was then dispersed in DI water to obtain a GO colloidal solution and probe-sonicated for 120 min via ultra-probe sonicator (Qsonica, Sunway Scientific Corporation, Hsinchu, Taiwan).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that Ag nanoparticles anchored on GO sheets can enhance bactericidal efficiency [ 8 , 15 , 16 ]. To date, in-depth antibacterial analyses of Ag NPrsms incorporated with GO have not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The key factors that merit significant consideration in a green synthetic route is its eco-friendliness, economic prospects, safety, facile, and feasibility justifying a promising future for this field (Rauwel, Küünal, Ferdov, & Rauwel, 2015).Silver nanoparticles are the typical and most ideal target in the field of green nanotechnology. It has swiftly gained infinite interest because of their widespread applications in catalysis (Tamuly, Hazarika, Bordoloi, & Das, 2013), electronics (Vasilevaa, Donkova, Karadjova, & Dushkin, 2011), sensors (Li, Wu, & Ong, 2005), and most importantly in antimicrobial (Truong et al, 2020;Umar et al, 2020), antifungal (Than et al, 2020), and anticancer (Lia, Natsuki, & Natsuki, 2020) applications. The antibacterial property of silver nanoparticles is due to the release of Ag + ions which interact with the bacterial membrane resulting in inhibition of cell growth, followed by DNA damage, and inhibiting the bacterial propagation.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene oxide (GO) is a two-dimensional functional material and one of the most widely used derivatives of graphene. In order to prevent the aggregation of AgNPs, the GO sheets could be loaded into AgNPs which will immobilize the formed silver nanoparticles (Than et al, 2020;Truong et al, 2020;Umar et al, 2020). Furthermore, GO possesses potent antibacterial activity against various pathogenic bacterial strains and also shows excellent cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%